Voting behavior of the people of Dharmasraya Regency in the 2019 presidential election: Perilaku memilih masyarakat Kabupaten Dharmasraya pada pemilihan presiden tahun 2019 - Prasetyo, Rino Adi (Universitas Airlangga, 2025)
This research is motivated by the declaration of support actions carried out by 12 regents and mayors in West Sumatra Province for the presidential candidate Joko Widodo – Ma’ruf Amin in the 2019 presidential election. Despite being endorsed by the winning party in Dharmasraya, PDI-P, and the Regent of Dharmasraya having declared support, Jokowi - Ma'ruf only obtained 30.69% of the votes, while Prabowo - Sandi secured 69.31% of the votes in Dharmasraya. Furthermore, Dharmasraya Regency has a multicultural society, with the majority of the population being of Minangkabau and Javanese ethnicities. Therefore, the research problems formulated in this study are: 1) How is the relationship between the declaration of support by the Dharmasraya Regent for the presidential candidate Joko Widodo-Ma’ruf Amin and the voting behavior of Dharmasraya's community in the 2019 Presidential Election; and 2) how is the relationship between ethnicity and the voting behavior of Dharmasraya's community in the 2019 Presidential Election. The theories utilized in this research are the rational choice theory of voting behavior and the sociological theory of voting behavior. The method employed is quantitative research with a explanatory study design. Data were collected through questionnaire distribution, and respondents were selected using multistage cluster random sampling method. Data analysis was performed using SPSS 26 with cross-tabulation analysis and hypothesis testing using the Chi-Square test. Based on these tests, it was concluded that the perception of the declaration of support (X1) has a significant relationship with a strong correlation to the variable of voting behavior of the Dharmasraya community (Y). Additionally, the ethnicity variable (X2) has a significant relationship with a moderate correlation to the variable of voting behavior of the Dharmasraya community (Y). Keywords: Voting Behavior, Dharmasraya, Ethnicity, Declaration of Support, Presidential Election. Abstrak: Penelitian ini dilatarbelakangi oleh adanya aksi deklarasi dukungan yang dilakukan oleh 12 Bupati dan Walikota di Provinsi Sumatera Barat kepada pasangan calon presiden Joko Widodo – Ma’ruf Amin pada Pilpres tahun 2019. Meskipun diusung oleh partai pemenang pemilu yaitu PDI-P, dan Bupati Dharmasraya sudah melakukan aksi deklarasi dukungan, ternyata Jokowi - Ma’ruf hanya memperoleh 30,69% suara, dan Prabowo - Sandi memperoleh 69,31% suara di Dharmasraya. Selain itu, Kabupaten Dharmasraya juga memiliki masyarakat yang multikultur, mayoritas penduduknya bersuku bangsa Minangkabau dan Jawa. Oleh karena itu, rumusan masalah dalam penelitian ini adalah: (1) Bagaimana hubungan deklarasi dukungan Bupati Dharmasraya kepada pasangan calon presiden Joko Widodo-Ma’ruf Amin dengan perilaku memilih masyarakat Dharmasraya pada Pemilihan Presiden Tahun 2019, dan (2) bagaimana hubungan antara etnisitas dengan perilaku memilih masyarakat Dharmasraya pada Pemilihan Presiden Tahun 2019. Teori yang digunakan dalam penelitian ini adalah teori perilaku memilih mazhab rasional dan teori perilaku memilih mazhab sosiologis. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif dengan jenis penelitian eksplanatif. Data diperoleh melalui penyebaran kuesioner, dan responden dipilih menggunakan metode multistage cluster random sampling. Analisis data menggunakan aplikasi SPSS 26 dengan analisis tabulasi silang serta pengujian hipoteses menggunakan uji hubungan Chi-Square. Berdasarkan pengujian tersebut makan diperoleh kesimpulan bahwa, persepsi deklarasi dukungan (X1) memiliki hubungan signifikan dengan kekuatan hubungan yang mantap terhadap variabel perilaku memilih masyarakat Dharmasraya (Y). Dan variabel etnisitas (X2) memiliki hubungan signifikan dengan kekuatan hubungan yang sedang terhadap variabel perilaku memilih masyarakat Dharmasraya (Y).